An Effective Model for Glueballs and Dual Superconductivity at Finite Temperature - Issifu, Adamu; Brito, Francisco A. (Advances in High Energy Physics, 2021)
The glueballs lead to gluon and QCD monopole condensations as by-products of color confinement. A color dielectric function G∣ϕ∣ coupled with a Abelian gauge field is properly defined to mediate the glueball interactions at confining regime after spontaneous symmetry breaking (SSB) of the gauge symmetry. The particles are expected to form through the quark-gluon plasma (QGP) hadronization phase where the free quarks and gluons start clamping together to form hadrons. The QCD-like vacuum η2mη2FμνFμν, confining potential Vcr, string tension σ, penetration depth λ, superconducting and normal monopole densities (ns nn), and the effective masses (mη2 and mA2) will be investigated at finite temperature T. We also calculate the strong “running” coupling αs and subsequently the QCD β-function. The dual superconducting nature of the QCD vacuum will be investigated based on monopole condensation.